Security in the twenty first century : a Bangladesh perspective - Osmany, Mufleh R.; Ahmad, Muzaffer; Bangladesh Institute of International and Strategic Studies (Dhaka : Academic Press and Publishers in association with Bangladesh Institute of International and Strategic Studies, 2003)
Contributed articles.
Strategy, a Bangladesh perspective / Mohammad Humayun Kabir -- National security of Bangladesh : the traditional context / A.K.M. Abdus Sabur -- Non-traditional security in Bangladesh : framework and issues / Abdur Rob Khan -- Maritime security of Bangladesh / Abul Kalam Azad.
"Published on the occasion of BIISS silver jubilee"--T.p. verso.
Includes bibliographical references.
Keywords: National security -- Bangladesh; Sea-power -- Bangladesh